Auditoria independente: impacto da qualidade dos lucros sobre os honorários de auditoria - Pinheiro, Renato Barros (2018)
In the current context of the securities market, the main role of financial audit statements is to secure the accounting information quality made available to the interested parties, knowing that such information is the basis for the decision-making process of those interested in relation for the reporting entity. Related to quality, the accounting information has among its critical points, the quality of the profits found inside it, which are related, from the perspective of the quality of the accruals, with the difference between the net income and the cash flow of each period, both of which represent information relevant for the stakeholders. Therefore, the earnings quality found in accounting information is a source of concern for independent auditors, as it might affect the audit risks and, as a consequence, have an impact on the determination of the auditors fees, assuming that the determination of fees should consider the risk of work. The objective of this research is to examine the influence of the quality on the profits to the determination of the independent auditors fees in Brazil. From the methodological view, according to the current literature, the goal was achieved followinf the Jones models Modified by Dechow, Sloan and Sweeney (1995), Dechow and Dichev (2002) as calculation metrics accruals and the Thomson Reuters Eikon® database was used, with annual companies observation listed in B3 from the period 2010 to 2015. The results evidence that audit fees are negatively related to the quality of earnings in the past period (t-1), in other words, the auditors incorporate audit fees into the cash flow risks associated with the quality of the profits identified at the time of hiring the service. On the other hand, the results also show a negative and significant relationship between audit fees and quality of earnings in the current period (t), that is, auditors demand an additional share as a premium to the cash flow conversion risks incurred during the duration of the audit contract.